Initial axillary surgery: results from the BreastSurgANZ Quality Audit. Issue 10 (20th November 2013) - Chong, Chilton; Walters, David; de Silva, Primali; Taylor, Corey; Spillane, Andrew; Kollias, James; Pyke, Chris; Campbell, Ian; Maddern, Guy
Abstract Background The aim of this study was to establish the preference and reasons for initial axillary surgery performed on women with invasive breast cancer in Australia and New Zealand using data from the Breast Surgeon's Society of Australia and New Zealand Quality Audit (BQA) according to whether sentinel lymph node (SLN) biopsy, axillary lymph node dissection (ALND) or no axillary surgery was used. Methods Patient data from 1999 to 2011 were categorized according to primary tumour size (≤3 cm or >3 cm) and analysed by year of diagnosis, type of initial axillary surgery and frequency of second axillary surgery following SLN biopsy. Patient age at diagnosis, health insurance status, surgeon caseload and hospital location were also examined as factors affecting the likelihood of performing different types of axillary surgery. Results Seventy thousand six hundred and eighty‐eight episodes of early breast cancer with axillary surgery data were reported to the BQA in the study period. The proportion of patients undergoing SLN biopsy as the first operation increased over this period in both tumour size groups with a concomitant decline in the use of ALND as the first operation over the same interval. Elderly women (>70 years old) were four times less likely to undergo axillary surgery for their initial management when compared with women aged 41–70 years old (P < 0.001). Factors favouring ALND as the initial surgery over SLN biopsy included larger tumour size, elderly age, uninsured status and having surgery in a regional centre. Conclusions From 1999 to 2011, SLN biopsy as the initial axillary surgery has been widely adopted by surgeons reporting to the BQA. Future evaluation of the BQA data in the following 3–5 years will be performed to monitor this progression.